2022
DOI: 10.1016/j.outlook.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Black nurse scientists and the undeniable role of historically Black colleges and universities

Abstract: The pandemics of COVID-19 and systemic racism highlighted health inequities that have existed for decades among Black communities. Nurses are positioned to address these health inequities through innovative ideas and research. More specifically, Black nurses, because of their shared lived experience, understand sociostructural factors underpinning health inequities and how to best engage with Black communities. However, only 8% of Black nurses make up the overall nursing workforce and far fewer are nurse scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Ethnic minorities, particularly Blacks and Hispanics were under-represented in the nursing workforce in many states, especially those in the South, including Mississippi, Alabama, South Carolina, and Louisiana. This has implications for health education delivery as health professionals from a given community may have more credibility in overturning strongly entrenched misinformation and vaccine hesitancy among members of their community, underscoring the need for cultural diversity in the workforce 14 . Furthermore, our secondary analyses indicated that the number of COVID-19 deaths per 100000 population decreased as the number of nurses to each COVID-19 hospitalized case increased.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic minorities, particularly Blacks and Hispanics were under-represented in the nursing workforce in many states, especially those in the South, including Mississippi, Alabama, South Carolina, and Louisiana. This has implications for health education delivery as health professionals from a given community may have more credibility in overturning strongly entrenched misinformation and vaccine hesitancy among members of their community, underscoring the need for cultural diversity in the workforce 14 . Furthermore, our secondary analyses indicated that the number of COVID-19 deaths per 100000 population decreased as the number of nurses to each COVID-19 hospitalized case increased.…”
Section: Discussionmentioning
confidence: 99%
“…10 Despite their limited number, there is a growing awareness and acknowledgment of their importance in ameliorating health disparities. Aycock and colleagues 29 highlighted the importance of AANSs in addressing these inequities through their research contributions. Although there is some research on Black nurse faculty and nursing students, there is little to no research that examines the experiences of AANSs that may include experiences with structural racism or captures their scholarly contributions 14,[17][18][19]30,31 Nonetheless, in an era of growing understanding and eradication of structural racism in nursing, a careful examination of the experiences of AANSs is warranted.…”
Section: Contributions Of African American Nurse Scientistsmentioning
confidence: 99%
“…In addition to addressing local needs in a given facility, clinical specialty associations, academic institutions, and philanthropic foundations frequently identify priorities for nursing inquiry that drive HCOs' and the national clinical research agenda. In recent years, gerontology, 2 genomics, [3][4][5] data science, 6 implementation science, 7 oncology, 4,8 health policy, 9 and health equity 10 were at the forefront of identified priority health issues for nursing science. Although the need for nursing science to develop new knowledge is clear, accountability and infrastructure to support nurse-led research are not.…”
mentioning
confidence: 99%